Analyzing Context in English as Lingua Franca (ELF): A Discourse Analysis in an Indonesian Higher Education Institution (HEI) - Wongso Adi Saputra (CV. Eureka Murakabi Abadi, 2022)
English as English as Foreign Language (EFL) in Indonesia makes the learners get the difficulties in exposing themselves to Native English Speakers (NESs) environment. Hence, EFL learners in Indonesia are only exposed to the Non-Native English Speakers (NNESs) condition that make use English as Lingua Franca (ELF) when talking using English. Furthermore, in using ELF, the learners should engage all context in their mind to smoothen the communication built using ELF. The context that the learners have is core context regarding their First Language (L1) instead of NESs. Hence, in the communication running, the learners attach emergent context in order to overcome the miss-communication found in the conversation. In order to see the process of emergent context, this study in “analyzing context in ELF: A Discourse Analysis in Indonesian Higher Education Institution (HEI)” is run by using discourse analysis on corpus data taken from two HEIs learners’ conversation in Indonesia. The data taken is analyzed, and the result is divided into reformulation and given/new. Furthermore, based on reformulation and given/new categories, it is shown that context especially Emergent context is appeared in two ELF used situation. They are in learning and in communication using ELF.